The everyday experiences of reconstruction and regeneration from vision to reality in Birmingham and coventry - Adams, David 1980-; Larkham, P. J. 1960- (Routledge, 2019)
Set within a wider British and international context of post-war reconstruction, The Everyday Experiences of Reconstruction and Regeneration focuses on such debates and experiences inBirmingham and Coventry as they recovered from Second World War bombings and post-war industrial collapse. Including numerous images, Adams and Larkham explore the initial development of the post-Second World War reconstruction projects, which so substantially changed the face of the cities and provided radical new identities. Exploring these cities throughout the post-war period brings into sharp focus the duality of contemporary approaches to regeneration, which often criticise mid-twentieth century 'poorly-conceived' planning and architectural projects for producing inhuman and unsympathetic schemes, while proposing exactly the type of large-scale regeneration that may potentially create similar issues in the future. This book would be beneficial for academics and students of planning and urban design, particularly those with an interest in post-catastrophe or large-scale reconstruction projects within cities